School furniture ergonomics : optimal design criteria for standard requirements in Malaysian education system / Abdul Halim Manaf - Manaf, Abdul Halim (2009)
The problem of design mismatch led to the enquiry of the study. The aim of the study is to determine the optimal design criteria of school furniture that match with user requirements and fulfill the learning system in Malaysia. By exploratory and descriptive research, the objective was to identify principles, elements and characteristics on design strategy and design features based on perceived evaluation of existing school furniture on desks and chairs focusing on 'User' from social ergonomics perspective. Therefore, field survey was conducted among User group participants (n = 2079, 895 boys and 1184 girls) from 4th year secondary public schools students in Klang Valley representing the Malaysian sample, including the School Management groups among the Education Ministry, School Administrator and Furniture Supplier. Both qualitative and quantitative research methods were adopted. Instruments used for gathering data interviews on design strategy were semi-structured questions; whereas on survey questionnaires of design features, interval scale rating methods were used to measure user satisfaction, problems and expectations. Specifically, the content analysis on school management reveals the major factor of dissatisfaction is poor structure and the existing school furniture design requires revision. Statistical data analysis by SPSS on user shows there are 5 principal components that emerged as the important factors of school furniture design criteria. Whereby, the mean level of satisfaction on the factors of 'general appearance', 'strength and durability', and 'usability' were below average except for 'anthropometry' as average; whereas, on the factor of 'health and safety', the mean level of problem occurs sometimes. Subsequently, the ranking order of user expectation reveals that 'comfort, health and safety' as the highest followed by 'image and appearance' as the least important. Overall results indicated that there is a mismatch between school furniture and the user requirements.